2022
DOI: 10.1177/07356331211052632
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Regulated Learning Support on Learners’ Task Performance and Cognitive Load in Computer Programing

Abstract: This study explores the effect of self-regulated learning support on learners’ cognitive load and problem-solving performance, considering cases from well-structured to ill-structured tasks in a computer programing course. Sixty-seven undergraduate students in a computer programing fundamentals course were randomly assigned into one of two groups: (1) experimental group ( N = 34; received self-regulated learning support) and (2) control group ( N = 33). Participants in both groups were asked to solve programin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
2
8
0
1
Order By: Relevance
“…However, that difference is not clear concerning our students with high school levels studying at the university. A potential explanation for our finding may be that students who have finished a high school level need to develop independent learning skills (Vosniadou, 2020), while students with university degrees may use more visual and verbal elaboration strategies due to the need to autonomously learn a large amount of information that imposes a high cognitive load (Chi et al, 1989;Mirza et al, 2019;Shin and Song, 2022).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, that difference is not clear concerning our students with high school levels studying at the university. A potential explanation for our finding may be that students who have finished a high school level need to develop independent learning skills (Vosniadou, 2020), while students with university degrees may use more visual and verbal elaboration strategies due to the need to autonomously learn a large amount of information that imposes a high cognitive load (Chi et al, 1989;Mirza et al, 2019;Shin and Song, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…One of the crucial aspects of school learning and lifelong learning is self-regulation, which means that students who use appropriate self-regulation strategies may learn more (Núñez Perez et al, 2006;Badali et al, 2022;Biwer et al, 2022;Jansen et al, 2022;Shin and Song, 2022). A basic premise of self-regulated learning is that there are regulatory processes (i.e., monitoring and control) that are performed on aspects associated with school learning, and can be understood, fostered, and even trained for being transferred to other learning tasks (Bell and Kozlowski, 2008;Usher and Schunk, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Program development is known to be a process that demands the use of multiple mental resources (Prather et al, 2020 ), and the impacts of incorporating scaffoldings that stimulate these resources simultaneously are unknown. Thus, we argue the importance of studying this phenomenon from the Cognitive Load Theory perspective (Mutlu-Bayraktar et al, 2019 ), as providing regulatory support could increase students’ cognitive load (Shin & Song, 2022 ). Nevertheless, how regulatory support influences cognitive load and its impact on learning still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of regulation of learning support is influenced by variables, such as students’ school level, the intervention focus (e.g., cognition, metacognition, motivation, or others), the presence of collaborative activities, among others (Dignath & Büttner, 2008 ; Theobald, 2021 ). In addition to these factors, SRL skills development may require time (Shin & Song, 2022 ). Therefore, these elements should also be pondered when analyzing the results from multiple studies.…”
Section: Discussionmentioning
confidence: 99%
“…SRL support helps learners achieve academic success, and its importance is demonstrated by studies that have shown that learners who lack SRL support may not regulate their learning to obtain an adequate level of understanding when studying complex topics (Azevedo & Hadwin, 2005; Shin & Song, 2022; Wang et al, 2022). Various forms of computer-based scaffolding have been proposed, such as prompts, feedback, and integrated support systems.…”
Section: Literature Reviewmentioning
confidence: 99%